CGIAR Platform for Big Data in Agriculture - Plan of Work and Budget 2020 - CGIAR Platform for Big Data in Agriculture (CGIAR Platform for Big Data in Agriculture, 2020)
The Platform for Big Data in Agriculture works towards outcomes demonstrating that CGIAR —as a more unified System—has claimed a leadership position in the evolving digital agriculture landscape. Some of these outcomes are internal and focused on organizational development, and some are focused on transformations CGIAR can effect in the sector through our extensive, collective, and global partnership networks. In these ways, the BIG DATA Platform has been building towards “One CGIAR” for close to three years. In 2020 the Platform will consolidate progress, assess the evidence and progress of initiatives to date, and propose a digital roadmap for the organization. 2021, the last year of the Platform in its current form, will embody the first year of that roadmap.